Integrating digital literacy in the disciplines - Hays, Lauren; Kammer, Jenna; Bruff, Derek (Stylus Publishing, LLC, 2021)
"Digital literacy has become the vital competency that students need to master before graduating. This book provides rich examples of how to integrate it in disciplinary courses"--